The measurement of the asymmetry of tensor-polarized deuteron electrodisintegration at 180 MeV electron energy; Physics Letters B; Vol. 188, iss. 2 - Mostovoy M. V.; Nikolenko D. M.; Ospanov K. T.; Popov S. G.; Rachek I. A.; Shatunov Yu. M.; Toporkov D. K.; Tsentalovich E. P.; Woitsekhowski B. B.; Zelevinsky V. G.; Naumenko G. A. Gennadiy Andreevich; Stibunov V. N. Victor Nikolaevich (1987, 1987)
Title screen